Social Media Risks and Benefits: A Public Sector Perspective. (October 2014) - Khan, Gohar Feroz; Swar, Bobby; Lee, Sang Kon
Social media are becoming an important intermediary for interaction between governments, governments and citizens, and governmental agencies and businesses. This is due to the unique characteristics of social media: openness, participation, and sharing. However, despite rapid adoption, a growing concern and skepticism regarding the use of social media exists in the public sector. The purpose of this study is to investigate empirically the risks and benefits of social media use by public agencies. For this purpose, a research model was developed and tested in a survey of 289 government sector employees from six South Korean government research institutes. We found that both risks (i.e., social risk, time, psychological risks, and privacy concern) and benefits (i.e., social connectivity, social involvement, information attainment, and entertainment) significantly affect public sector employees' satisfaction with and intention to use social media. However, the effect of the benefits on users' satisfaction was stronger than the risks. The results of the study have important implications for researchers and policy makers.